À la recherche du paysage dans la « forêt monumentale » de Guyane française à travers la culture amérindienne - Fabienne Boursier (Projets de Paysage)
More than 90% of French Guyana is covered by forests. This provides an opportunity for comparing the French notion of the landscape with that of the Amerindian population - the “first people” of the Amazonian region - thanks to a study of their cosmogony and their experience of this space. This study is based on bibliographical research and seeks to find out if there exists a “vision of the forest landscape” among the Wayana, Wayãpi and Teko, on the basis of toponymic and aesthetic notions. The perspective of the French authorities is examined in view of conducting a comparative study. The study is also an attempt to explain why this forest cannot be considered as a single “cultural landscape”. The missions of the Amazonian Park of Guyana, where the Wayana, Wayãpi and Teko live, are presented and in the last part of the article, the notion of forest heritage, closely related to that of the cultural landscape, is discussed.